Ultraconserved Elements Occupy Specific Arenas of Three-Dimensional Mammalian Genome Organization - Ruth B. McCole; Jelena Erceg; Wren Saylor; Chao-ting Wu (Cell Reports, 2018)
Summary: This study explores the relationship between three-dimensional genome organization and ultraconserved elements (UCEs), an enigmatic set of DNA elements that are perfectly conserved between the reference genomes of distantly related species. Examining both human and mouse genomes, we interrogate the relationship of UCEs to three features of chromosome organization derived from Hi-C studies. We find that UCEs are enriched within contact domains and, further, that the subset of UCEs within domains shared across diverse cell types are linked to kidney-related and neuronal processes. In boundaries, UCEs are generally depleted, with those that do overlap boundaries being overrepresented in exonic UCEs. Regarding loop anchors, UCEs are neither overrepresented nor underrepresented, but those present in loop anchors are enriched for splice sites. Finally, as the relationships between UCEs and human Hi-C features are conserved in mouse, our findings suggest that UCEs contribute to interspecies conservation of genome organization and, thus, genome stability. : McCole et al. demonstrate the non-random relationship between the positions of perfectly conserved genomic regions, termed the ultraconserved elements (UCEs), and three-dimensional genome organization within mammalian nucleus as defined by Hi-C studies. They postulate that these connections aid in orchestrating genome packaging and preserving genome function and integrity. Keywords: Hi-C, chromosome organization, ultraconserved elements, UCEs, copy number variants, CNVs, kidney, exons, RNA processing